Polyurethane and lumbang oil production - Borromeo, Melissa-Sieglinde E. (College of Engineering, 1987)
The polyurethanes are among the most recent and promising resins to achieve prominence in the coatings field. This field only became popular after the second World War. With the increasing production of polyurethane in the 1950's up to the present, more uses for it were discovered. As of now, there is no polyurethane manufacturer in the country yet. Besides, some manufacturers have given up importing polyurethane despite the fact that they are of better quality because of the high cost of this product. The high quality of polyurethane, its growing use and the absence of local manufacturer led the group to this study. Aside from that, the raw materials to be used is also very common in the country. From the market study taken from NCSO, it was found out that the demand for crude and refined lumbang oil grows at an interest rate of 8 percent and 3.36 percent respectively. The data for linseed oil was used because it can be substituted for lumbang oil and no available data for lumbang oil consumption could be found. As early as 1965, the world's demand for polyurethane was already about 1,500 M lbs. This value might have increased greatly by now because of the growing application of urethane. For Philippine consumption, the growth rate of polyurethane is also increasing. The plant will be situated in Nasipit, Agusan del Norte and along Butuan Bay for easier shipment of materials. Aside from that, Butuan City is also the source of raw materials. Some other advantages are the low cost of water and electricity. The process used is simply a combination of some basic reactions and a few laboratory findings about the hydroxylation process of lumbang oil. It should be understood that the research about polyurethane is not developed yet especially in our country. The process design is the simplest and the most direct to the point the group could obtain. The plant is almost a two-in-one plant with different processes. The first unit is the oil extraction process. Here, the oil is expelled from the lumbang seed and further recovered from the pressed meal. It then undergoes further purifications. The second process is the urethane formation. This process is made up of two main reactions. The first is the hydroxylation reaction of lumbang oil with NaCl0 to produce a halchydrin. The hydroxylated product then undergoes various purification processes. The second reaction is the polymerization reaction. The pure hydroxylated product is reacted with an isocyanate to produce urethane. The polyurethane product is then stored in heated tanks to prevent solidification. The plant will contain utilities and waste disposal unit. There are not much utilities needed because steam and electricity will both be purchased. The utilities unit will only contain a water treater for the process water and a stand-by generator in case there is power failure. Process water will be obtained from the nearby river. It will be economized by making it pass through various exchangers in both units before being discarded. The plant will operate continuously for 360 days a year. All the equipment will be supplied by a local fabricator. So as the pumps and conveyors. The economic evaluation showed that the project is feasible. It will have a payback period of 5.26 years. This is only true however, for the present production. If the production is increased to the plant's full capacity the project is unfeasible. This is due mainly to the high cost of reagents used in the process. As soon as there are better findings about polyurethane, the production cost is sure to be cut down by a great degree and the increase in production will be feasible.